Physical exercise and cardiac death due to pneumonia in male teenagers - Duraković, Zijad (Array, 2009)
Abstract: From 1998 to 2008 we noticed 3 cardiac deaths in male teenagers aged 18–19 during or after physical exercise. The first was working at the site recreatively, the second was engaged in soccer recreativelyand the third was professional soccer player. One felt general tiredness and was exhausted of a heavily physical effort, the other after physical exercise became septic and the third was without symptoms. One died suddenly during physical exercise at the field and two died in the hospital. At the forensic autopsy the first had bilateral bacterial pneumonia, possible high-altitude non-cardiogenic pulmonary edema and cerebral edema. The second had bilateral bacterial pneumonia, adult respiratory distress syndrome, disseminated intravascular coagulation, suprarenal bleeding, cerebral edema, hypoplastic right coronary artery and myocardial fibrosis. The third had bilateral bacterial pneumonia, fibrinous pericarditis, cerebral contusion with edema, thickenning of the left ventricle 20 mm and hypoplastic ascending aorta. In Croatia the death rate among athletes reached 0.15/100 000, in athletes suffered of acute pneumonia 0.28/100 000, in others who practice exercise recreatively 0.57/100 000 (p=0.0068), in all males who practice exercise recreatively 0.75/100 000 (p=0.0014). Physical exercise is contraindicated in acute respiratory tract infections. Every such case has to be treated by physician. When to start with physical training after bacterial pneumonia depends on dissapearing of clinical and X-ray signs of pneumonia, normalization of erythrocite sedimentation rate and of white cell count